2011
DOI: 10.1080/13607863.2011.583625
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-experimental design trial exploring the effect of a partnership intervention on family and staff well-being in long-term dementia care

Abstract: Participation in the FIC intervention improved family caregiver knowledge. The major barrier to the success of the partnership intervention in achieving beneficial long-term psychosocial effects for family and staff caregivers was lack of resources and leadership required to support collaboration between family and staff, mainly due to environment and structural changes. This study contributes to our understanding of the importance of partnerships in promoting family involvement in dementia care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 42 publications
3
51
1
3
Order By: Relevance
“…Similar to previous studies (Bramble et al, 2011; Maas et al, 2004; McCallion et al, 1999; Pillemer et al, 2003; Robinson et al, 2007), we also found that caregiver knowledge about end-stage ADRD and long-term care increased. In addition, we expected that increased knowledge coupled with decreased guilt would mediate a decrease in caregiver conflict with facility staff.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to previous studies (Bramble et al, 2011; Maas et al, 2004; McCallion et al, 1999; Pillemer et al, 2003; Robinson et al, 2007), we also found that caregiver knowledge about end-stage ADRD and long-term care increased. In addition, we expected that increased knowledge coupled with decreased guilt would mediate a decrease in caregiver conflict with facility staff.…”
Section: Discussionsupporting
confidence: 90%
“…The eight caregivers, whose spouses had been placed in long-term care (7) or had died (1) post-intervention, did not maintain these positive effects at the 8-month follow-up (Ott et al, 2010). These findings further support existing evidence that post placement, dementia caregivers continue to experience new losses, guilt, and role captivity (Bramble, Moyle, & Shum, 2011; Maas et al, 2004). …”
Section: Chronic Grief In Adrd Caregiverssupporting
confidence: 85%
See 1 more Smart Citation
“…This is particularly the case in situations: where work pressures challenge family; the distance to the long-term care facility may inhibit opportunity to spend time with their family member; and, family may feel they have a limited role in the provision of care [4,5]. Opportunities to connect families and people with dementia living in long-term care may now be made possible through new technologies such as telepresence robots.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, staff should be given opportunities to reflect on their practice, particularly as regards to workload and time management, and staff and team relationships (McCormack et al, 2010). This will also reduce potential tensions between staff and family members, and improve the LTC experience for both (Pashby et al, 2009;Bramble et al, 2011;Moyle et al, 2013b;Moyle et al, 2014). This will also reduce potential tensions between staff and family members, and improve the LTC experience for both (Pashby et al, 2009;Bramble et al, 2011;Moyle et al, 2013b;Moyle et al, 2014).…”
Section: Discussionmentioning
confidence: 99%